Benchmarking process of knowledge management best practice model for higher learning institution - Ismail, Halijah; Abdullah, Rusli; Jusoh, Yusmadi Yah (School of Computing, College of Arts and Sciences, Universiti Utara Malaysia, 2016)
This paper aims to propose the benchmarking process for KM Best Practice Model to suits Higher Learning Institution (HLI) environment. The need for Benchmarking of KM Best Practice Model is due to the lack of research made to confirm the Best KM Model for HLI. Benchmarking process will helps HLI to ensure continuous improvement and hopefully will uplift KM state in HLI by implementing benchmarked KM Best Practice Model due to the stagnant state of KM in HLI for the past 10 years. Method: Literature for Benchmarking were extracted to propose the right benchmarking process for HLI environment. Several KM models were extracted from the literature and reviewed. The KM Model were selected to suit the HLI environment in Malaysia, this is to ensure the KM Model selected served as the best KM model to be practice in the future or practically named internal benchmarking. Conclusion: The paper proposed Benchmarking process for KM Best Practice Model to suits HLI. The moderator for KM Best Practice Model were identified to proceed with the KM Best Practice Components effectiveness validation in the future study. This study also proposed a conceptual Model for KM Best Practice.